Acne vulgaris in adolescents - the review - Aleksandra Wójcik; Sylwiusz Niedobylski; Joanna Wrona; Daria Madycka; Kinga Wnuczek; Jakub Starownik; Kacper Michta (Nicolaus Copernicus University in Toruń, 2024)
Acne vulgaris is one of the most common chronic inflammatory skin disorders that affects almost 90% of the adolescents worldwide. Due to its effect on one's appearance, it causes not only physical but also psychological consequences. The cause of acne involves increased sebum production, hyperkeratinisation of the follicle, bacterial colonization and inflammation, which result in formation of comedones, papules, pustules and nodules. Diet, Body Mass Index, hyperhidrosis and stress can be triggering factors. The pharmacological treatment of acne involves substances administered topically as well as orally. First line of treatment of mild-to-moderate acne involves topical benzoyl peroxide, retinoids, chemical peels, antibiotics and combinations of those agents. The treatment of moderate-to-severe or inflammatory acne consists of oral antibiotics, isotretinoin, oral contraceptives and spironolactone. New therapies are being investigated and show a great potential, however further research should be pursued in order to achieve long-lasting results of the treatment.